The influence of electrical dynamic range in cochlear implants of children at age 3 years on speech perception, vocabulary and quality-of-life outcomes at age 9 years. - Ching, Teresa Y. C.; Hou, Sanna; Incerti, Paola (International Journal of Audiology, 2025)
Objectives: To investigate 1) the influence of electrical dynamic range (DR) in cochlear implants (CI) of children at 3 years of age on their speech perception, vocabulary, and health-related quality of life (HRQOL) at 9 years of age; and 2) changes in electrical stimulation levels and DR over the first 10 years of life. Design: This is a prospective longitudinal study on outcomes of children with congenital hearing loss. Outcomes at 9 years were measured using standardised tests. Generalised linear models were used to examine the effects of DR in CIs at age 3 years on children's 9-year outcomes. Study sample: One hundred and two children who received CIs before 3 years of age. Results: On average, vocabulary and HRQOL were within the range of typically hearing peers. A wider DR at 3 years was associated with better self-rated HRQOL at 9 years of age. Parent-proxy ratings of HRQOL were higher for children with better vocabulary. Earlier CI activation was associated with better speech perception and vocabulary. DR was stable over time. Conclusion: The findings lend support to early cochlear implantation and emphasise the importance of optimising stimulation levels and DR at a young age to maximise longer-term outcomes.